A decepção de Tinker Bell e a luta das classificações: o artesanato, o Governo Federal e o Sebrae - Maria Salete de Souza Nery (Ciências Sociais Unisinos)
Based on the Conceptual Basis of Brazilian Handicraft, a document published by the Ministry of Development, Industry and Foreign Trade (MDIC), and on the Reference Term of the Sebrae System in Arts and Crafts, both from 2010, we seek to problematize the issue of ratings and the struggles that are at stake in the channeling of values and practices in arts and crafts. Taken as accepted and consensual, the term handicraft is a place of disputes, particularly in its tension with art and the market. We outline the role and the power of the State in defining the legitimate meanings that regulate coordinated ac- tions of differenta agencies and also of the individuals who are considered craftsmen. Thus, we ask: What are the clashes present in the definition of handicraft and what are the positions assumed by seminal agents about this? The documents cited above are the basis to highlight these issues and also the difficulties and dilemmas of the government and Sebrae as partners in the task of promoting handicraft and they help us to discuss, even in introductory terms, the possible meanings of this partnership.